La estimulación cognitiva como estrategia para desarrollar las funciones ejecutivas básicas de un niño con discapacidad intelectual, de la Escuela de Educación Básica Especializada María Auxiliadora, Catamayo 2020 -2021. - Pérez Rodríguez, Odalis Carolina (2022)
In the follwing curricular integration study called “Cognitive Simulation as a strategy to develop basic functions with an intelectual disability child from the Maria Auxiliadora Primary School, Catamayo 2020-2021”, whose aim is to analyze the process of cognitive simulation as a strathegy tu help within the progress of the basic functions of a intelectual disability child. This study has a qualitative approach which was base don a case of study, likewise, it is considered descriptive with a cross section, where instruments such as: participatory obserbation, interviews, EFECO questionnaire, field journal and some archivements records were used. Due to the aplication of the previous instruments, the results obtained allowed us to identify this child`s strengths and weaknesses within behavioal areas such as basic repeoires (imitation, following instructions and attention), social and adaption skills (personal care), verbal and behavior problems, which were confirmed through the application of interviews with the teacher as well as the mother and within the process, also being able to observe that those executive functions are deficient in flexibility, working memory, self-control of emotions and inhibition, obtaining a resulto f 21%, available by the application of thr instrument mentioned. Nevertheless, thanks to the application of cognitive simulation strategies, some achievements were accomplished withinthe behavior áreas of basic repertoires (following instructions and attention), in the behavior área of social and adaption skills (personal care) and behavior problems, as well as the functions, reaching an increase of 89%. Considering all this, it may be ssaid that the application of cognitive simulation stragies responds to the needs of the child´s school education in order to enhance their behavior áreas and functions, because it Will support as well as improve the infant`s life quality. Keywords: cognitive stimulation, executive functions, behavioral areas.